ANALYSIS OF THE INFLUENCE OF THE SHARIA PERSPECTIVE ON THE RELATIONSHIP BETWEEN PARENTS AND CHILDREN IN ENSURING FUTURE ECONOMIC RESILIENCE: REVIEW OF SHARIA ECONOMIC LAW BASED ON SDG 8 - Alfiana, Chatrine Yorda; Muthoifin, Muthoifin (istinbath, 2025)
Objective: This study aims to examine the concept of relationship and economic responsibility of parents to children from the perspective of Sharia economic law as a foundation in building economic resilience for future generations in line with the SDGs. Theoretical framework: In order to understand the mechanism of intergenerational financial resources in accordance with the principles of Islamic economic law, the theoretical framework integrates sharia concepts, specifically the principles of Hifz al-Malh (preserving property) and Hifz al-Nasl (protecting offspring). Literature Review: The literature review examines how Muslim parents can help children develop a positive economic mindset through tarbiyah māliyah, or Islamic financial education. The study also highlights the low level of knowledge about Sharia contracts among Indonesian Muslim families and the need for orphan protection. The report also emphasizes the importance of accountability and transparency in the management of orphan assets in social institutions such as orphanages. Methodology: This study applies normative legal research methods, with a conceptual and legislative approach, by examining the Qur'an, Hadith, juristic views, and various literature on Sharia economic law. The analysis was carried out in a qualitative descriptive manner to examine the relationship between economic responsibility in the family and sustainable economic resilience based on the perspective of the SDGs. Results: According to the study's findings, families who incorporated Islamic financial education into their Sharia parenting practices had financial resilience up to 23% greater than non-Sharia households. However, implementing the best Sharia economic practices remains difficult, as the basis of Sharia contracts is not well established in about 65% of cases. Transparency and remote experience issues in orphan asset management. Implications: In addition to proposing policies to improve Islamic financial literacy and to strengthen monitoring systems for the competent and fair management of orphan assets, the study emphasizes the importance of incorporating Islamic financial education into childcare to improve families' long-term economic resilience. Newness: The novelty of this study lies in its emphasis on the practice of sharia economic education, applied by parents to children in the family environment, as an effort to prepare children for future financial sustainability, with an analysis from the perspective of sharia economic law.